2019
DOI: 10.1038/s41597-019-0071-0
|View full text |Cite
|
Sign up to set email alerts
|

An ATAC-seq atlas of chromatin accessibility in mouse tissues

Abstract: The Assay for Transposase-Accessible Chromatin using sequencing (ATAC-seq) is a fundamental epigenomics approach and has been widely used in profiling the chromatin accessibility dynamics in multiple species. A comprehensive reference of ATAC-seq datasets for mammalian tissues is important for the understanding of regulatory specificity and developmental abnormality caused by genetic or environmental alterations. Here, we report an adult mouse ATAC-seq atlas by producing a total of 66 ATAC-seq profiles from 20… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
112
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(126 citation statements)
references
References 42 publications
14
112
0
Order By: Relevance
“…Changes in chromatin conformation and accessibility are widespread during development where cells undergoing differentiation exhibit major alterations in gene expression [1]. Consistent with this, comparison of chromatin differences between cell types by ATAC-seq has identified large numbers of regions of differing accessibility [28], supporting previous findings ,using the similar DNase I sensitivity assay, that chromatin accessibility at expression quantitative trait loci (eQTLs) is the major determinant of human expression variation [29]. Many such accessible regions overlap with enhancer modifications confirming the cell type specific regulation of gene expression by enhancers.…”
Section: Discussionmentioning
confidence: 71%
“…Changes in chromatin conformation and accessibility are widespread during development where cells undergoing differentiation exhibit major alterations in gene expression [1]. Consistent with this, comparison of chromatin differences between cell types by ATAC-seq has identified large numbers of regions of differing accessibility [28], supporting previous findings ,using the similar DNase I sensitivity assay, that chromatin accessibility at expression quantitative trait loci (eQTLs) is the major determinant of human expression variation [29]. Many such accessible regions overlap with enhancer modifications confirming the cell type specific regulation of gene expression by enhancers.…”
Section: Discussionmentioning
confidence: 71%
“…Since ChIP-seq experiments showed a correlation between the strength of transcription and H2A.Z enrichment at the TSS, we can conclude that in muscle cells, as in any cell type, a correlation exists between transcription strength and chromatin accessibility. ChIP-seq and ATAC-seq alignment further indicated that in muscle fibers, as in other mouse tissues 32 , chromatin was the most accessible between the +1 and the -1 nucleosomes surrounding the TSS (Fig. 2D).…”
Section: Invalidation Of H2az-1 and H2az-2 Inmentioning
confidence: 80%
“…The ATAC-seq data were processed (trim, alignment, filter, and QC) using the ATAC-seq pipeline from the Kundaje lab 31,32 (Table 2). The model-based analysis of ChIP-seq (MACS2) 33 version 2.1.2 was used to identify the peak regions with options −B, −q 0.01 -- nomodel, −f BAM, −g mm.…”
Section: Methodsmentioning
confidence: 99%